Recent advances in fecal microbiota transplantation for Clostridium difficile infection-associated diarrhea after kidney transplantation - Li, Yurong; Yang, Yaoyao; Yang, Ning; Wu, Qin; Yang, Jinjin; Guo, Jing; Zhang, Hongmei (Frontiers in Microbiomes, 2024)
Kidney transplantation is considered to be the best treatment for end-stage renal disease. To reduce the incidence of rejection and improve the survival of recipients and kidney grafts, kidney transplant recipients must take immunosuppressive agents, and some patients require them for the rest of their lifetime. These treatment regimens can result in susceptibility to opportunistic infections and disrupt the intestinal microbiota, thereby leading to diarrhea, which causes water and electrolyte metabolism disorder, nutrient malabsorption, and instability in the blood concentrations of the immunosuppressive agents. Fluctuating blood concentration levels of these agents necessitate frequent laboratory monitoring and dose adjustments to avoid poor adherence and increase the risk of graft rejection. Furthermore, severe diarrhea can cause kidney transplant failure or death. Clostridium difficile infection (CDI) is the leading cause of diarrhea after renal transplantation. Traditional antibiotics can kill C. difficile; however, spores can remain in the gut. Disruption of the intestinal flora caused by antibiotherapy increases the risk of developing recurrent CDI (rCDI). Fecal microbiota transplantation (FMT) has been proven to be a safe and effective treatment for CDI and is recommended for rCDI owing to its convenient material acquisition method, high efficacy, and low incidence of adverse reactions. This review summarizes the recent progress in FMT for CDI-associated diarrhea after renal transplantation.